Superoxide Dismutase from Marine as a Cytotoxic Agent - Apriani, Dwi Wulan; Indrayati, Ana; Herdwiani, Wiwin; Rendati, Hema Novita; Zulfah, Khairina (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2024)
The prevalence of cancer in Indonesia has shown an increase from 1.4 per 1000 population in 2013 to 1.79 per 1000 population in 2018. 70% of our planet is covered by unparalleled air and marine biodiversity. Therefore, medical researchers have focused on the marine world which has great potential, in the last six decades (Sagar et al. 2010). To find out other uses of biota, it is necessary to study the SOD of marine biota that reacts with their metal cofactors, to determine the specific SOD of some biota, to determine the SOD cytotoxic activity of several marine biota, to determine the mechanism of SOD of marine biota as anticancer. This literature review was carried out in several stages: formulating problems, collecting, evaluating, analyzing, and synthesizing data. The data sources used are international journals from publishers such as Science Direct, Elseiver, and SpringerLink between 2010 and 2021. The literature results obtained for the SOD classification of marine biota based on metal cofactors are 1,092 articles. The articles obtained will be selected and 52 articles that meet the inclusion criteria will be reviewed. The results of the search for specific SOD activities from marine biota were obtained by 1,243 articles. 13 articles that meet the inclusion criteria and will be reviewed. The results of the search for SOD cytotoxic activity from marine biota obtained 2,199 articles. 7 articles that met the inclusion criteria will be reviewed. The search results for specific SOD activities from marine biota were 2,496 articles. 8 articles that meet the inclusion criteria and will be reviewed. The results showed that SOD from marine biota had cytotoxic activity.